As Dimensões do cuidado no processo de trabalho dos enfermeiros na Atenção Primária à Saúde - Ferreira Cícero Lima, Bruna; Silva da Costa, Fabiano; Marina Rabelo, Erika; Machado Torres, Lilian; Pereira de Almeida, Shirley (BEPA. Boletim Epidemiológico Paulista, 2020)
.